Octopus : the ocean's intelligent invertebrate - Mather, Jennifer A.; Anderson, Roland C.; Wood, James B. (Portland, Or. : Timber Press, 2010)
A natural history of the octopus, featuring personal narratives, underwater research, and closeup photography that details mating and predatory behaviors, intelligence, and problem-solving abilities.
Introduction: Meet the octopus -- In the egg -- Drifting and settling -- Making a living -- In the den -- Getting around -- Appearances -- Not getting eaten -- Personalities -- Intelligence -- Sex at last -- The rest of the group -- Postscript: Keeping a captive octopus.
Includes bibliographical references (pages 189-200) and index.
Keywords: Octopuses